2014
DOI: 10.12691/jfnr-2-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Berry Extracts on Hydrogen Peroxide-induced Rat Brain Neuronal Cell Damage in vitro

Abstract: The purpose of this study was to evaluate the antioxidative activities and protective effects of boysenberry, black currant, and blueberry extracts on neuronal cells. We found that berry extracts had different levels of antioxidant efficacy in various assays, including cell viability assays using 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl-tetrazoliumbromide (MTT). In addition, reactive oxygen species (ROS) were measured using 2',7'-dichlorofluorescein diacetate (DCF-DA) and flow cytometry analysis. Fruit extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In our study, we observed that JPE pretreatment was able to prevent the increase of •NO induced by H 2 O 2 and this prevention was more effective at the concentration of 50 μg mL −1 (Table 3). These data are in line with other studies that showed the ability of other berries, such as strawberries, black currants and boysenberries, to minimize the oxidative damage induced by H 2 O 2 in mammalian cells (Ho & Chang, 2005;Jeong et al, 2014).…”
Section: Componentssupporting
confidence: 92%
“…In our study, we observed that JPE pretreatment was able to prevent the increase of •NO induced by H 2 O 2 and this prevention was more effective at the concentration of 50 μg mL −1 (Table 3). These data are in line with other studies that showed the ability of other berries, such as strawberries, black currants and boysenberries, to minimize the oxidative damage induced by H 2 O 2 in mammalian cells (Ho & Chang, 2005;Jeong et al, 2014).…”
Section: Componentssupporting
confidence: 92%
“…To determine the antioxidant activity of garlic extracts, hepatoma cells were exposed to 200 μmol/L H 2 O 2 (Kemika, Zagreb, Croatia) to induce oxidative stress ( 14 , 15 , 16 , 17 , 18 , 19 , 20 ). The protective effect of garlic extracts was evaluated by adding CG and PG extracts to a cell culture medium 20 min after cell exposure to H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Anthocyanins have a high oxygen radical absorption capacity (ORAC) value, which may partially account for the neuroprotective effect [168,169]. Similarly, in in vitro models of H2O2 injury and Aβ peptide-induced toxicity, anthocyanins directly scavenge intracellular ROS formation [166,170]. Moreover, the indirect intrinsic antioxidant activity of anthocyanins may be due to (i) the restoration or increase in endogenous antioxidant enzymatic activities (SOD, CAT, and GPx) [171,172,173] resulting in higher antioxidant glutathione levels [174]; (ii) the activation of these endogenous antioxidants along with phase II detoxification genes by activating the antioxidant response element (ARE) via the redox-sensitive transcription factor NF-E2-related factor-2 (Nrf2) [175,176]; or (iii) the reduction in oxidative adduct formation in DNA and reduction in endogenous ROS formation by inhibiting xanthine oxidase and NADPH oxidase or by modifying arachidonic metabolism and mitochondrial respiration [165,177].…”
Section: Anthocyanins: a Natural Antioxidantmentioning
confidence: 99%